2021
DOI: 10.1093/pubmed/fdab173
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with work performance and mental health of healthcare workers during pandemics: a systematic review and meta-analysis

Abstract: Introduction Healthcare workers’ work performance and mental health are associated with positive mental health outcomes and directly related to increased productivity and decreased disability costs. Methods We conducted a systematic review to identify factors associated with work performance of healthcare workers during a pandemic and conducted a meta-analysis of the prevalence of mental health outcomes in this context. Primary papers were collected and analysed using the Population/Intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 46 publications
0
45
0
2
Order By: Relevance
“…The literature search detected a total of 458 articles (228 after removal of duplicates) and after having scrutinized 106 out of 228 articles for depth eligibility, we finally included 44 articles (meta-analyses) in this umbrella review ( Adibi et al, 2021 , Al Maqbali et al, 2021 , Alimoradi et al, 2021a , Alimoradi et al, 2021b , Arora et al, 2020 , Bareeqa et al, 2021 , Batra et al, 2020 , Cenat et al, 2021 , da Silva and Neto, 2021 , Deng et al, 2021 , Dong et al, 2021 , Dubé et al, 2021 , Dutta et al, 2021 , El-Qushayri et al, 2021 , Galanis et al, 2021 , Hao et al, 2021 , Jahrami et al, 2021a , Jahrami et al, 2021b , Krishnamoorthy et al, 2020 , Li et al, 2021 , Luo et al, 2020 , Mahmud et al, 2021 , Marvaldi et al, 2021 , Nowrouzi-Kia et al, 2021 , Olaya et al, 2021 , Pappa et al, 2020 , Phiri et al, 2021 , Raoofi et al, 2021 , Ren et al, 2020 , Salari et al, 2020a , Salari et al, 2020b , Salazar de Pablo et al, 2020 , Salehi et al, 2021 , Santabárbara et al, 2021 , Saragih et al, 2021 , Serrano-Ripoll et al, 2021 , Singh et al, 2021 , Sun et al, 2021 , Troglio da Silva and Neto, 2021 , Varghese et al, 2021 , Wu et al, 2021 , Xia et al, 2021 , Yan et al, 2021 , Zhang et al, 2021 , Zhao et al, 2021 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search detected a total of 458 articles (228 after removal of duplicates) and after having scrutinized 106 out of 228 articles for depth eligibility, we finally included 44 articles (meta-analyses) in this umbrella review ( Adibi et al, 2021 , Al Maqbali et al, 2021 , Alimoradi et al, 2021a , Alimoradi et al, 2021b , Arora et al, 2020 , Bareeqa et al, 2021 , Batra et al, 2020 , Cenat et al, 2021 , da Silva and Neto, 2021 , Deng et al, 2021 , Dong et al, 2021 , Dubé et al, 2021 , Dutta et al, 2021 , El-Qushayri et al, 2021 , Galanis et al, 2021 , Hao et al, 2021 , Jahrami et al, 2021a , Jahrami et al, 2021b , Krishnamoorthy et al, 2020 , Li et al, 2021 , Luo et al, 2020 , Mahmud et al, 2021 , Marvaldi et al, 2021 , Nowrouzi-Kia et al, 2021 , Olaya et al, 2021 , Pappa et al, 2020 , Phiri et al, 2021 , Raoofi et al, 2021 , Ren et al, 2020 , Salari et al, 2020a , Salari et al, 2020b , Salazar de Pablo et al, 2020 , Salehi et al, 2021 , Santabárbara et al, 2021 , Saragih et al, 2021 , Serrano-Ripoll et al, 2021 , Singh et al, 2021 , Sun et al, 2021 , Troglio da Silva and Neto, 2021 , Varghese et al, 2021 , Wu et al, 2021 , Xia et al, 2021 , Yan et al, 2021 , Zhang et al, 2021 , Zhao et al, 2021 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some factors related to the risk of contagion in the organizational workplace and the adoption of preventive procedures [such as the lack personal protective equipment (PPE), the conflict between safety procedures and the desire to provide support, increased and heavy workload with multitasking as well as longer working hours, negative emotion of patients, distance of families, and fears of infection for themselves and their families] can deeper affect the mental well-being of these frontline healthcare workers during the COVID-19 epidemic ( 14 , 53 ); and in response, when selecting interventions aimed at supporting frontline health workers' mental health, organizational, social, personal, and psychological factors might all be important reported in a systematic review ( 55 ), and thus, multiple organizational and work-related interventions (such as improvement of workplace infrastructures, the adoption of correct and shared anti-contagion measures), psychological support interventions (such as counseling and psychology services) and multifaceted interventions were recommended to help mitigate this scenario ( 53 , 55 ). Furthermore, a systematic review further revealed that young age, and female gender, and heavy workload were the factors increasing the risks of suffering from post-traumatic stress symptoms in healthcare workers dealing with the COVID-19 pandemic ( 56 ), whereas negative mental health outcomes were associated with diminished work performance ( 57 ), and therefore, hospital managers should also pay more attention to these physicians in “high workload and high self-assessment” subtype, who were younger, female, participated in aiding in the COVID-19 pandemic, and even experienced mental health problems during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID‐19) pandemic continues to place a high demand on healthcare workers who are already highly susceptible to burnout due to the tense work environment and many responsibilities 6‐9 . Our recent systematic review and meta‐analysis identified nine factors associated (e.g., depression, anxiety, decreased productivity, and burnout) with work performance among healthcare workers including physicians, nurses, and allied health professionals 10 . The increased workload exacerbates the situation and leads to increased work exhaustion, job dissatisfaction, and turnover rates 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Our recent systematic review and meta-analysis identified nine factors associated (e.g., depression, anxiety, decreased productivity, and burnout) with work performance among healthcare workers including physicians, nurses, and allied health professionals. 10 The increased workload exacerbates the situation and leads to increased work exhaustion, 4.82), high work life conflict (OR = 5.08, 95% CI: 2.75-9.64) and high job satisfaction (OR = 0.43, 95% CI: 0.20-0.88), high self-rated health (OR = 0.32, 95% CI: 0.17-0.56) were significant. job dissatisfaction, and turnover rates.…”
Section: Introductionmentioning
confidence: 99%